THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL PRODUCTIVITY IN HYBRID WORK ENVIRONMENTS - Juliandi Saputra; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid global shift to hybrid work models has necessitated a re-examination of the well-established link between employee engagement and organizational productivity. This study investigated this relationship through a mixed-methods approach, combining a quantitative survey of knowledge workers with qualitative interviews. The results confirmed a strong positive correlation (r=.65) between engagement and productivity, with dedication being the strongest predictor. However, a critical paradox emerged: office-centric employees reported the highest engagement, while fully remote employees reported the highest productivity. Flexibly remote employees (1-2 office days) constituted a vulnerable "middle-child" group with the lowest scores in both. The discussion highlights that engagement drivers have shifted, requiring intentional connection, managerial trust, and equity of experience. We conclude that the hybrid model reconfigures, rather than severs, the engagement-productivity link, demanding strategic, rather than one-size-fits-all, management practices to navigate this new paradigm.